The ergonomics virtual reality station design (ErgoVR) - Taha, Z.; Yap, H.J.; Raja Ghazilla, R.A.; Ahmad, N. (2009)
Virtual reality (VR) is a promising technology which has the ability to immerse a user in a virtual world through the use of 3D real time computer graphics. The user works "together" with the virtual objects to complete the desired task. Therefore. a physical environment is needed to make the users feel. see and interact with virtual objects in the most natural and ergonomic position so that the unnecessary awkward posture and others physical discomfort that could be detrimental to the users of the virtual system can be avoided. The objective of this research is to design an Ergonomic virtual reality station that will reduce the unnecessary awkward posture and others physical discomfort when using VR system. Anthropometries data was collected from Malaysian population. Statistical analysis was conducted to analyze the uniformity of anthropometries data and required number of sample. Result of the research shows that the appropriate design to the anthropometries data of users will be able to reduce the awkward posture and others physical discomfort.